Effect of postlearning meditation on memory consolidation: level of focused attention matters - Collins, Megan B. (Learn Mem, 2020)
Recent studies demonstrate that eyes-closed rest benefits memory consolidation, perhaps due to reduced attention to environmental stimuli. Here, we asked whether focusing attention to internal thoughts and feelings after learning similarly blocks memory consolidation. Verbal memory was tested following an eyes-closed consolidation period filled with either focused attention to breath or quiet rest. Although breath-focus did not impair memory relative to quiet rest overall, participants who reported being more successful in maintaining breath-focus during this condition showed increased forgetting. We interpret these findings as incompatible with a simple sensory-interference-based account of rest's effect on memory.